Chilenos, peruanos y bolivianos en la pampa: 1860-1880 ¿Un conflicto entre nacionalidades? - Osorio Gonnet, Cecilia (Historia, 2001)
The present study intends, by analyzing the cases provided by the historical sources, to explain and delve into the characteristics of the coexistence between Chilean, Peruvian and Bolivian unskilled workers in the nitrate mining environment that existed prior to the War of the Pacific. In difficult working conditions and a no less hostile desert, the relationship was not easy. Certain conflictive issues have come to be regarded as nationalist, specially considering the circumstances that preceded the war. However, the denomination is not accurate. The following investigation’s goal is to analyze this environment in its varied and complex characteristics, questioning traditional conceptualizing as well as proposing a new lecture that considers the diverse variables available